Flow Behavior of Isolate Protein from Soybeans var. Grobogan and Whey Protein Isolate at Acidic Condition under Various Heating Times - Warji Warji; Sutrisno Suro Mardjan; Sri Yuliani; Karin Schroën; Nanik Purwanti (PERTETA, 2018)
AbstractFlow behavior of Soy Protein Isolate (SPI) suspension and Whey Protein Isolate (WPI) solution at pH 2.0 under various heating times were studied using steady shear viscosity measurements. Shear rate sweeps with increasing shear rates (up ramp) was performed to investigate the structural breakdown of the proteins during shearing. Down ramp shear rates were performed to check structural recovery of the proteins. The results showed that unheated SPI suspension has Newtonian flow; meanwhile, unheated WPI solution was slightly shear thickening. Heating the proteins at 80ºC for 4, 8, 12, and 16 h changed flow behavior of the proteins. Flow curve of SPI suspension heated for 12 h and 16, fitted Ostwald model with flow behavior index (n) of 0.625 and 0.264, respectively. This index indicates pseudoplastic (shear thinning) behavior, which also observed in heated WPI solution. The changes in flow behavior was attributed by the changes in protein structures, i.e., globular structures into fibrillar structures under prolonged heating at acidic condition. This conversion also increased the apparent viscosities of the proteins. SPI fibrils have higher apparent viscosities than WPI fibrils. This difference might be attributed to the detail fibril structures. SPI fibrils have branched and curvy structures; meanwhile, WPI fibrils are long and straight.AbstrakPerilaku aliran suspensi Soy Protein Isolate (SPI) dan larutan Whey Protein Isolate (WPI) pada pH 2.0 pada berbagai lama pemanasan diinvestigasi. Shear rate yang meningkat diaplikasikan untuk mengetahui kerusakan struktur protein selama geseran. Shear rate dengan pola menurun dilakukan untuk mengetahui apakah strukturprotein kembali ke struktur awal setelah mengalami kerusakan. Hasil penelitian menunjukkan bahwa suspensi SPI yang tidak dipanaskan memiliki perilaku aliran Newtonian; sementara larutan WPI yang tidak dipanaskan bersifat sedikit shear thickening. Pemanasan protein pada 80ºC selama 4, 8, 12, dan 16 jam mengubah perilaku aliran suspensi SPI dan larutan WPI. Kurva aliran suspense SPI yang dipanaskan selama 12 jam dan 16 jam sesuai dengan model Ostwald dengan indeks perilaku aliran (n) masing-masing 0.625 dan 0.264. Indeks ini mengindikasikan perilaku aliran bersifat pseudoplastic (shear thinning), yang juga teramati pada larutan WPI yang dipanaskan. Perubahan perilaku aliran disebabkan oleh perubahan struktur protein dimana SPI dan WPI awalnya memiliki struktur globular lalu menjadi struktur fibrillar akibat pemanasan yang lama pada kondisi asam. Perubahan struktur juga meningkatkan nilai apparent viskositas, dimana viskositas fibril SPI lebih tinggi daripada fibril WPI. Perbedaan ini diakibatkan oleh perbedaan struktur fibril protein dimana SPI berbentuk fibril yang bercabang dan melengkung sedangkan WPI berbentuk fibril yang lurus dan panjang.